An insight into plant-based yogurts: Physicochemical, organoleptic properties and functional food aspects - Qadir, Rahman; Wan Mohamad Nasir, Wan Nur Afifah; Azmi, Aliah Batrisyia; Fatima, Seemal; Mehmood, Naunain; Meor Hussin, Anis Shobirin (Academic Press, 2025)
Plant-based yogurts have become a popular dairy-free alternative, appealing to consumers with dairy allergies and those motivated by ethical considerations. This review article examines the key ingredients, formulations, physicochemical traits, organoleptic properties, and functional food values of plant-based yogurts in comparison to dairy-based yogurt. It focuses on the key challenges such as optimal nutritional composition, acidity, water holding capacity, desirable texture, flavor, and probiotic viability, while exploring emerging technologies and fortification strategies aimed at improving these aspects. Plant-based yogurts often require optimization to match the protein content, probiotic activity, and micronutrient composition of dairy-based yogurt. Advances in current ingredient selection and processing methods continue to close the gap between existing and desired food textures while addressing production challenges. In addition, research suggests that plant-based yogurts may offer several health advantages such as an improved immune system, better gut health, and reduced risks of various chronic diseases. Continued innovation and research are, however, essential to refine the sensory and nutritional aspects of plant-based yogurts, ensuring they meet the growing consumer demands.